Micologia no dia a dia: uma abordagem do estudo dos fungos na educação de jovens e adultos - Rabelo, Elias Augusto Vieira (2022)
Teaching about fungi in basic education is almost always carried out in a fragmented, decontextualized and superficial perspective. In this way, this work presents itself as a contribution to this problem and was developed at the Benedita Targino Maranhão State School of Elementary and High School with classes of EJA (Youth and Adult Education) of cycles V and VI Medium, through new practices and pedagogical strategies for the teaching of Biology in the Mycology area, aiming, from the students' prior knowledge, to promote meaningful learning in the classroom, demystifying the negative perceptions about fungi. Therefore, the objective of this work was to develop and apply a didactic sequence about fungi, using active teaching methodologies in promoting student autonomy and raising awareness about the importance of the topic. For this, a qualitative research was carried out, in which the forms of data collection were conversation circles, participant observation and focus group. The didactic sequence developed was contextualized with the daily life of the students of the EJA modality to promote scientific literacy and break with the purely traditional, content and technical teaching. For this, the sequence began with an expository class, followed by a round of questions and the creation of a conceptual map on the typical characteristics of fungi, in order to raise the students' prior knowledge. After that, an investigative work of analysis of videos made available by the teacher about the general importance of fungi was proposed. Then, a support text provided by the teacher was analyzed and posters were made about the relationship between fungi and the discovery of medicines, such as penicillin. In addition, the students watched a video lesson produced by the teacher about mycoses to later fill out forms containing information about a certain disease from case studies made available by the teacher. Finally, a debate was held followed by the development of a game about the economic importance of fungi. Due to the COVID-19 pandemic, activities were adapted so that they could be developed remotely and, if there was an opportunity, in person. In view of this scenario and limitations, 12 of the 45 students in the chosen groups responded to the first application of the questionnaire and 4 students responded to the second application of the questionnaire. Thus, after the application of the didactic sequence, there was a significant improvement in the percentage of correct answers in the questionnaires, compared to the first and second application. This improvement shows that it is possible, through active teaching and learning strategies, to promote and encourage student protagonism in High School in EJA classes.